EuPtSn2 – A Stannide with Sn2 Dumbbells in a Three‐dimensional [PtSn2]2– Polyanion. Issue 3 (29th August 2019) - Klenner, Steffen; Stegemann, Frank; Pöttgen, Rainer
Abstract : EuPtSn2 was obtained by melting of the elements in a sealed tantalum ampoule followed by an annealing sequence for crystal growth. The EuPtSn2 sample was studied through its Guinier powder pattern and the structure was refined from single‐crystal X‐ray diffractometer data: CeRhSn2 type, Cmcm, a = 472.05(3), b = 1724.19(12), c = 957.36(7) pm, wR 2 = 0.0388, 879 F 2 values and 30 variables. The platinum and tin atoms build up a three‐dimensional [PtSn2 ] 2– polyanionic network which consists of distorted PtSn5 square pyramids (265–278 pm Pt–Sn) and Sn2 dumbbells with 281 and 299 pm Sn–Sn distances. The structural relationship with DyRhGe2 and Ce3 Pt4 Ge6 is discussed. EuPtSn2 shows Curie–Weiss behavior with an experimental magnetic moment of 7.78(1) μB / Eu, indicating stable divalent europium. This is corroborated by 151 Eu Mössbauer spectroscopy. Antiferromagnetic ordering is detected below 3.4 K. Specific heat measurements confirm the magnetic ordering and indicate a second phase transition through a clear λ‐type signal at 7.3 K which might be associated with a structural distortion. Abstract :